Performance Evaluation of Air Sterlizer - Ansari, Md. I A; Datta, A K (Journal of Agricultural Engineering, 2006)
Sterilized air has an important role in aseptic pouch packaging machine. The main use of sterilized air is in maintaining sterile condition in the filling and a slight positive pressure in relation to the environment, and in removing excess H2O2 from the packaging material surfaces. In present study, an air sterilizer was designed and its performance was evaluated. The test was carried out with natural microflora. The bacterial count at velocity of 40; m/s varied from 0 to 42; at 30 m/s air velocity, bacterial count varied from 0 to 35 while at 20 m/s, it was found to vary from 0 to 20 cfu/mÂ³. Bacterial counts were found to be zero above 100 Â°C at all velocity. The hot air, free from any bacterial load, was used in aseptic pouch packaging machine for different purposes.